Pengembangan Media Pembelajaran Matematika Menggunakan Macromedia flash Pada Materi Bangun Ruang Sisi Datar di SMP Negeri 2 Lingsar - Putri Husnul Khotimah; Ketut Sarjana; Amrullah; Sri Subarinah (Pendidikan Matematika FKIP Universitas Mataram, 2022)
The purpose of developing this learning media is to produce an appropriate Macromedia Flash learning media on the flat side space building material at SMP Negeri 2 Lingsar. This learning media is based on the development of Multimedia Luther based on six stages, namely concept, design, collection (collecting material), assembly, testing, and distribution. This learning media test is a validity test, practical test, and beta test (user). The validity test was carried out by 2 media experts. The media experts in this study were 1 Lecturer of the Mathematics Education Study Program, University of Mataram and 1 Teacher of ICT Subjects at SMP Negeri 2 Lingsar. The practical test was carried out by 2 practitioners, namely 1 Lecturer of the Mathematics Education Study Program, University of Mataram and 1 Mathematics Subject Teacher at State Junior High School. 2 Lingsar, and beta test based on the results of a questionnaire filled out by 74 students. The instrument indicators are based on Thorn's feasibility test. The overall average validity test results are 3.14 in the very good category, the overall average practitioner test results are 3.39 in the very good category, the overall average beta test results are 2.86 in the good category. So it can be concluded that this learning media is suitable for use in learning mathematics.